The Use of a Large Multi-Touch Surface for Classroom Education. - Boardman, Stephen. (2017)
Abstract: Touch surfaces and devices have made their way into educational settings in large touch format such as SMART Board®, as well as smaller formats such as the Apple iPad®. While these devices are successful in the classroom, their uses are limited by their design. The Playsurface is a large format multi-touch surface which uses image processing instead of resistive and capacitive technologies to allow any object that reflects infrared light to be detected and tracked by the table. This design difference coupled with the upright, table-top format promotes multiple simultaneous users interacting with the table using more than physical touches. This thesis focuses on the development of educational applications utilizing tangible objects that are aimed at stimulating student engagement and collaboration between group members. Three educational applications were developed: two investigate the motion of objects and the third investigates robotic control theories. These applications were tested in two high school classrooms with a total of 12 participants. The feedback and suggestions from this testing are used to advise future work on the use of tangible objects in conjunction with multi-touch surfaces in education.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Christopher Rogers, and Ethan Danahy.; Committee: Chistopher Rogers, Ethan Danahy, and Daniel Hannon.; Keywords: Mechanical engineering, and Education.